Dynamics of soil organic carbon and nitrogen following agricultural abandonment in a karst region. Issue 1 (25th January 2017) - Li, Dejun; Wen, Li; Yang, Liqiong; Luo, Pan; Xiao, Kongcao; Chen, Hao; Zhang, Wei; He, Xunyang; Chen, Hongsong; Wang, Kelin
Abstract: Agricultural abandonment is regarded as a major driver of soil organic carbon (C) dynamics, but the mechanisms underlying the direction and magnitude of soil C dynamics following agricultural abandonment are poorly understood. Here dynamics of soil C and N contents during postagricultural succession were investigated in areas underlain by dolomite or limestone by using a space‐for‐time substitution approach in a karst region, southwest China. One hundred twenty‐five sites from cropland, grassland, shrubland, and secondary forest were selected to represent different succession stages. Overall, soil C and N contents were greater ( P < 0.05) over limestone than over dolomite mainly due to significantly greater contents of soil C and N in the cropland and grassland underlain by limestone. Both soil C and N contents were lowest in the cropland while highest in the forest. Further analysis indicated that the patterns of soil C and N dynamics differed between the two lithology types. Soil C and N contents increased significantly from cropland to forest over dolomite, while varied insignificantly among succession stages over limestone. Exchangeable calcium explained most of soil C and N variance. We proposed that higher dissolution rate of limestone could replenish the lost calcium so that the calcium levels, and in turn soil C and N contents, were stable from the cropland to the forest. Nevertheless, due to relatively low dissolution rate for dolomite, the calcium level was depleted in the cropland. Following agricultural abandonment, calcium level recovered due to decreased loss, which in turn resulted in recovery of soil C and N. Key Points: Soil C and N contents are greater over limestone than over dolomite Soil C and N contents increase after agricultural abandonment over dolomite but not over limestone Exchangeable Ca is key in controlling soil C and N dynamics following agricultural abandonment